IMPROVING THE EFFICIENCY OF THE FINANCIAL CONTROL SYSTEM IN TERMS OF THE RISK-ORIENTED MODEL - M. N. Ponkratova (Модернизация, инновация, развитие, 2016)
The imperfection of the legislative and methodological basis of fi nancial control in the Russian Federation shall determine the list of issues on illicit and misuse of budget funds, including with the use of schemes for the withdrawal of capital abroad through fi nancial instruments (cash, Bank transfers and deposits, securities and bills of exchange) operations which are common practice in our country. In this regard, of particular importance is the use of a risk-oriented model of financial control, adapted to the conditions of the Russian Federation.The article discusses the risk-based model as part of a system of financial control. The concept model aimed at check point, implying the identification of reference points in the organization's and customers' risk event.